Helicobacter pylori and corpus gastric pathology are associated with lower serum ghrelin - Mantero, Paula (2018)
AIM To evaluate the association of Helicobacter pylori (H. pylori ), cagA genotype, and type of gastric pathology with ghrelin, leptin and nutritional status. METHODS Fasted dyspeptic adults (18-70 years) referred for an upper digestive endoscopy were enrolled in this crosssectional study. Height and weight were assessed for body mass index (BMI) calculation. A sociodemographic survey was administered and nutrient intake was evaluated with 24 h dietary recalls. Serum total ghrelin and leptin levels were analyzed by enzymelinked immunosorbent assay. 13 C-Urea Breath Test was performed and four gastric biopsies were obtained during endoscopy for histopathology and H. pylori DNA amplification and genotyping. Data analysis was performed using X 2 , Mann-Whitney U , Kruskal-Wallis tests, Spearman´s correlation and linear regression. RESULTS one hundred and sixty-Three patients (40.8 ± 14.0 years), 98/65 females/males, were included. Overall, persistent H. pylori prevalence was 53.4% (95%CI: 45.7%-65.8%). Neither nutrient intake nor BMI differed significantly between H. pylori positive and negative groups. Serum ghrelin was significantly lower in infected patients [median 311.0 pg/mL (IQR 230.0-385.5)] than in uninfected ones [median 355.0 pg/mL (IQR 253.8-547.8)] (P = 0.025), even after adjusting for BMI and gender (P = 0.03). Ghrelin levels tended to be lower in patients carrying cagA positive strains both in the antrum and the corpus; however, differences with those carrying cagA negative strains did not reach statistical significance (P = 0.50 and P = 0.49, respectively). In addition, the type and severity of gastric pathology in the corpus was associated with lower serum ghrelin (P = 0.04), independently of H. pylori status. Conversely, leptin levels did not differ significantly between infected and uninfected patients [median 1.84 ng/mL (0.80-4.85) vs 1.84 ng/mL (0.50-5.09), (P = 0.51)]. CONCLUSION H. pylori infection and severity of gastric corpus pathology are associated with lower serum ghrelin. Further studies could confirm a lower ghrelin prevalence in cagA-positive patients.